2012
DOI: 10.1002/aic.13752
|View full text |Cite
|
Sign up to set email alerts
|

Are 3‐D models necessary to simulate packed bed reactors? analysis and 3‐D simulations of adiabatic and cooled reactors

Abstract: Simulations and analysis of transversal patterns in a homogeneous three‐dimensional (3‐D) model of adiabatic or cooled packed bed reactors (PBRs) catalyzing a first‐order exothermic reaction were presented. In the adiabatic case the simulation verify previous criteria, claiming the emergence of such patterns when (ΔTad/ΔTm)/(PeC/PeT) surpasses a critical value larger than unity, where ΔTad and ΔTm are adiabatic and maximal temperature rise, respectively. The reactor radius required for such patterns should be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…These models predict formation of stable 2-D (transversal) and 3-D spatiotemporal patterns such as band, antiphase, rotating, and pulse motion under adiabatic conditions. 26,[29][30][31]37 The long periods of oscillations predicted in these studies were in agreement with experimental observations. Intricate features of these complex motions have primarily been attributed to strong interactions between several underlying modes.…”
Section: ■ Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…These models predict formation of stable 2-D (transversal) and 3-D spatiotemporal patterns such as band, antiphase, rotating, and pulse motion under adiabatic conditions. 26,[29][30][31]37 The long periods of oscillations predicted in these studies were in agreement with experimental observations. Intricate features of these complex motions have primarily been attributed to strong interactions between several underlying modes.…”
Section: ■ Introductionsupporting
confidence: 86%
“…Models that use, in addition to local temperature and concentration, detailed rate expressions for the underlying kinetics such as adsorption–desorption and surface microkinetic mechanisms for CO oxidation and a periodic blocking-reactivation mechanism for ethylene hydrogenation have been considered. These models predict formation of stable 2-D (transversal) and 3-D spatiotemporal patterns such as band, antiphase, rotating, and pulse motion under adiabatic conditions. , , The long periods of oscillations predicted in these studies were in agreement with experimental observations. Intricate features of these complex motions have primarily been attributed to strong interactions between several underlying modes.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…For this reason, recent works are often motivated to add more physical meaning to their models. This allows to additionally focus on effects of secondary order (e.g., flow maldistributions, localized hot-spots, spatial and spatiotemporal patterns) (Sheintuch, 1997;Trinh and Ramkrishna, 1997;Jaree et al, 2001;Papadias et al, 2001;Marwaha and Luss, 2003;Agrawal et al, 2007;Viswanathan et al, 2008;Nekhamkina and Sheintuch, 2012), which is, however, not object of this work. Similarly, stable oscillatory solutions are also disregarded in this work, since they are unlikely to occur in fixed-bed reactors on an industrial scale due to their high thermal inertia (Jensen and Ray, 1982).…”
Section: State-space Multiplicitymentioning
confidence: 99%
“…In this study, we consider the formation of spatiotemporal patterns in non-adiabatic, catalytic packed-bed reactors. Nekhamkina and Sheintuch showed that, for a homogeneous model with first-order exothermic kinetics, under non-adiabatic conditions, at best only axisymmetric patterns such as targets can be obtained. Using a periodic blocking–reactivation kinetic model, we predict formation of a rich variety of spatiotemporal patterns, such as rotating patterns and spirals, in shallow, non-adiabatic packed-bed reactors.…”
Section: Introductionmentioning
confidence: 99%